The Effect of Administrated Infused Water of Red Dragon Fruit (Hylocereus polyrhizus (F.A.C. Weber) Britton & Rose) on Growth Performance of Broiler Chickens - Susanto, Adi; Aditya, Nico Chandra; Damayanti, Sari'ah Cintami; Saragih, Hendry (Faculty of Veterinary Medicine Universitas Brawijaya, 2021)
The use of synthetic Antibiotics Growth Promoters (AGP) in broiler rearing causes long-term negative effects. The use of red dragon fruit-infused water (IWBNM) as a natural supplement is necessary. Determine the effect of IWBNM on the growth of broiler chickens was the aim of this study. A completely randomized design using five groups with three replications was the research design used. Each replication consist of 20 chicken. IWBNM is administered through drinking water. The treatment was carried out for 21 days. The treatment consisted of P0 (Control) plain water: P (Treatment) concentration of dragon fruit. The treatment group is 1 = 0.25%; 2 = concentration 0.5% ; 3 = concentration 1% ; 4 = 2% concentration. The data was tested by One Way ANOVA, with the Least Significant Difference (LSD) test and Duncan as a follow-up test. The result showed that one ml of IWBNM contains a total flavonoid of 676,19 Âµg. Giving IWBNM for 21 days, in general, can improve the growth performance of broiler chickens. Measurement of morphometry and body weight on day 21 indicates the increasing growth performance of broiler chickens with the highest performance was achieved by the P4 group compared to P1, P2, P3, and P0. As for the ratio of visceral organs to body weight, IWBNM had no significant effect on both the heart and liver.